COMPARATIVE STUDY OF ANTHROPOMORPHIZED ANIMAL CHARACTERS IN ENGLISH AND UZBEK ANIMATION - Jumaniyozova Sarvinoz Rasulbekovna; Atkamova Sumanbar Askarovna (Ta'lim innovatsiyasi va integratsiyasi, 2026)
Abstract This article offers a structured side-by-side look at how human-like animal characters are used in English and Uzbek animated films, using a language-teaching and semiotics perspective. Instead of simply describing what’s on screen, it sets out clear criteria—what the characters’ speech is used for, how independently they act, how much symbolic meaning they carry, and how closely they match the story’s moral message—to see how anthropomorphism works both for storytelling and for teaching. Building on systemic-functional linguistics (Halliday) and cultural semiotics (Lotman), the study reviews six well-known animated works from each tradition. The results suggest that English animation tends to use anthropomorphism to show problem-solving and emotional intelligence, while Uzbek animation uses it more as a tool for moral lessons and for strengthening a shared group identity. The article also considers how these findings could be used in language classes and in teaching cross-cultural media literacy.